2015
DOI: 10.1002/2014jc010253
|View full text |Cite
|
Sign up to set email alerts
|

On the coefficients of small eddy and surface divergence models for the air‐water gas transfer velocity

Abstract: Recent studies suggested that under low to moderate wind conditions without bubble entraining wave breaking, the air-water gas transfer velocity k 1 can be mechanistically parameterized by the nearsurface turbulence, following the small eddy model (SEM). Field measurements have supported this model in a variety of environmental forcing systems. Alternatively, surface divergence model (SDM) has also been shown to predict the gas transfer velocity across the air-water interface in laboratory settings. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 42 publications
5
57
1
Order By: Relevance
“…This coupling agrees with observations that k w scales with the turbulent kinetic energy dissipation at the sea surface (ε), and that ε is better reflected by the sea state [54,56]. Accordingly, the COARE 3.0 included the wave state in the estimation of the roughness parameters essential for the transfer of mass, heat and momentum [69].…”
Section: Transfer Velocity Estimates From Field Datasupporting
confidence: 83%
See 3 more Smart Citations
“…This coupling agrees with observations that k w scales with the turbulent kinetic energy dissipation at the sea surface (ε), and that ε is better reflected by the sea state [54,56]. Accordingly, the COARE 3.0 included the wave state in the estimation of the roughness parameters essential for the transfer of mass, heat and momentum [69].…”
Section: Transfer Velocity Estimates From Field Datasupporting
confidence: 83%
“…With the optional coupling of the sea state and wind velocity forcings (through the iWLP joint estimate of z0 and u*), the FuGas enables an enhanced representation of local conditions that was demonstrated to be fundamental for the estimation of transfer velocities in fetch-limited situations [50,55,57]. This coupling agrees with observations that kw scales with the turbulent kinetic energy dissipation at the sea surface (ε), and that ε is better reflected by the sea state [54,56]. Accordingly, the COARE 3.0 included the wave state in the estimation of the roughness parameters essential for the transfer of mass, heat and momentum [69].…”
Section: Transfer Velocity Estimates From Field Datasupporting
confidence: 72%
See 2 more Smart Citations
“…Equation appears to hold across a wide range of marine and coastal systems (Zappa et al, ) with α = 0.4, though variations reported in the literature are by no means small ( α = 0.17 − 0.63), as discussed elsewhere (Tokoro et al, ; Vachon et al, ). Some studies amended α with a logfalse(εfalse) multiplier or a Reynolds number dependency (Wang et al, ), while others suggested that these amendments may be due to changes in exponent n with surface wind conditions (Esters et al, ). When the most efficient waterside momentum transporting eddy scales with Kolmogorov variables (labeled as microeddies), then dimensional considerations alone recover equation for n = 1/2 without invoking complex transport schemes (Lorke & Peeters, ) such as surface renewal (Lamont & Scott, ; Soloviev, ).…”
Section: Introductionmentioning
confidence: 99%